Estudo funcional in vitro de fibroblastos sinoviais de pacientes com artrite reumatoide, osteoartrite e grupo controle após estimulação com diferentes concentrações de TNF-alfa, Interleucina-1beta e Interleucina-33 - Camilla Ribeiro Lima Machado (2015)
Introduction: Rheumatoid arthritis and osteoarthritis are chronic joint diseases that are manifested by inflammatory, structural and functional articular changes. In synovial environment, synovial fibroblasts are involved in estrututal-synovitis damage cycle through production of inflammatory cytokines and cartilage degrading enzymes, metalloproteinases (MMPs). Objectives: To evaluate the production of IL-6, MMP-1 and MMP-3 and the activation of intracellular signaling pathways after stimulation by IL33, TNF-alpha and IL-1 beta insynovial fibroblasts of patients with rheumatoid arthritis, osteoarthritis and control group without arthritis. Methodology: Fibroblasts were cultured synovial tissue and synovial fluid of patients with rheumatoid arthritis, osteoarthritis and controls without arthritis. After 22 hours of stimulation with TNF-alpha 1; 5; 10 and 50 ng/ml, IL-1beta 0.1; 0.2; 0.3; 0.5 and 1 ng/ml and IL-33 1; 3; 10; 30; 100 ng/ml proceeded dosages of IL-6, MMP-1 and 3 by ELISA. The cell lysate of MAPK was evaluated by the phosphorylation kinases JNK, p38, ERK1/2 and transcription factors (NF-kB) stimulated with TNF-alpha 10 ng/ml, IL-1beta 0,1 ng/ml and IL-33 100 ng/ml for 15 and 30 minutes by Western blot technique. Results: Cultures of synovial fibroblasts of patients with rheumatoid arthritis, osteoarthritis and control group without arthritis, the non-stimulated cells had basal production of MMP-1, MMP-3 and IL-6, and the stimulated cells with increasing concentrations of TNF-alpha and IL-1beta agonists induced production of MMP-1, MMP-3 and IL-6 after 22 hours. Afterstimulation by TNF-alpha and IL-1beta was observed phosphorylation of ERK1/2 and NF-kB. Stimulation with IL-33 did not induce IL-6, MMP-1 and -3 production in patients with rheumatoid arthritis, osteoarthritis and control group without arthritis, even at concentrations up to 100 ng/mL. In addition, this slight increase in the phosphorylation of ERK1/2 and NFkBin rheumatoid arthritis and osteoarthritis, was not sufficient to induce the production of metalloproteinase and IL-6. Conclusion: Synovial fibroblasts exert effector role in synovitis and structural damage ofrheumatoid arthritis and osteoarthritis. The behavior of human synovial fibroblasts in response to stimulation with IL-1beta and TNF-alpha seems to be mediated by pathways ERK1/2 and NF-kB, representing opportunity to study of new therapeutic targets.